Migration, trade, capital and development: substitutes, complements and policies - Gustav Ranis (Yale University, Economic Growth Center, 2007)
Migration of the unskilled clearly benefits the origin country, mainly due to the flow of remittances but also if the departure of some raises the ability of others to migrate. This depends on whether trade is a complement or a substitute for migration. The impact of such flows on the destination country is more ambiguous, although most research indicates that wages and employment are not likely to be seriously affected. Migration of the skilled is ambiguous with respect to the origin country since the impact of brain drain on local development must be weighed against the signaling effect for additional education plus the contribution of remittances. With respect to the destination country, the inflow of skilled labor is generally considered an unambiguous plus as it contributes to the enhancement of productivity. The paper concludes with policy recommendations aimed at seizing the opportunities arising from the fact that international migration remains the most constrained element of globalization.
Keywords: O11; O15; 330; Migration; trade; globalization